CONCEPTION OF A DEVICE FOR CARRYING OUT OF NEAR-SURFACE LASER PHORESIS - A. A. Ryzhevich; S. V. Solonevich; T. A. Zheleznyakova (Приборы и методы измерений, 2015)
We developed a conception of the electronic-optical device for carrying out of the nearsurface laser phoresis procedure using the dynamical gradient light field (DGLF) of the interference type. To select an optimal construction we considered some variants of devices for formation of the such DGLFs. In the framework of a model of biological tissues with nonequilibrium radiation absorption by its microstructures we calculated the general form of the temperature response dependence on the coherence ratio of the affecting DGLF. We proposed a criterion for choice of a laser source on the coherence ratio of its radiation for near-surface laser phoresis with DGLF.